Optimization and validation of automated hippocampal subfield segmentation across the lifespan. Issue 2 (23rd November 2017) - Bender, Andrew R.; Keresztes, Attila; Bodammer, Nils C.; Shing, Yee Lee; Werkle‐Bergner, Markus; Daugherty, Ana M.; Yu, Qijing; Kühn, Simone; Lindenberger, Ulman; Raz, Naftali
Abstract: Automated segmentation of hippocampal (HC) subfields from magnetic resonance imaging (MRI) is gaining popularity, but automated procedures that afford high speed and reproducibility have yet to be extensively validated against the standard, manual morphometry. We evaluated the concurrent validity of an automated method for hippocampal subfields segmentation (automated segmentation of hippocampal subfields, ASHS; Yushkevich et al., 2015b ) using a customized atlas of the HC body, with manual morphometry as a standard. We built a series of customized atlases comprising the entorhinal cortex (ERC) and subfields of the HC body from manually segmented images, and evaluated the correspondence of automated segmentations with manual morphometry. In samples with age ranges of 6–24 and 62–79 years, 20 participants each, we obtained validity coefficients (intraclass correlations, ICC) and spatial overlap measures (dice similarity coefficient) that varied substantially across subfields. Anterior and posterior HC body evidenced the greatest discrepancies between automated and manual segmentations. Adding anterior and posterior slices for atlas creation and truncating automated output to the ranges manually defined by multiple neuroanatomical landmarks substantially improved the validity of automated segmentation, yielding ICC above 0.90 for all subfields and alleviating systematic bias. We cross‐validated the developed atlas on an independent sample of 30 healthy adults (age 31–84) and obtained good to excellent agreement: ICC (2) = 0.70–0.92. Thus, with described customization steps implemented by experts trained in MRI neuroanatomy, ASHS shows excellent concurrent validity, and can become a promising method for studying age‐related changes in HC subfield volumes.